Resting-state network organisation in children with traumatic brain injury. (September 2022) - Botchway, Edith; Kooper, Cece C.; Pouwels, Petra J.W.; Bruining, Hilgo; Engelen, Marc; Oosterlaan, Jaap; Königs, Marsh
Abstract: Children with traumatic brain injury are at risk of neurocognitive and behavioural impairment. Although there is evidence for abnormal brain activity in resting-state networks after TBI, the role of resting-state network organisation in paediatric TBI outcome remains poorly understood. This study is the first to investigate the impact of paediatric TBI on resting-state network organisation using graph theory, and its relevance for functional outcome. Participants were 8–14 years and included children with (i) mild TBI and risk factors for complicated TBI (mild RF+, n  = 20), (ii) moderate/severe TBI ( n  = 15), and (iii) trauma control injuries ( n  = 27). Children underwent resting-state functional magnetic resonance imaging (fMRI), neurocognitive testing, and behavioural assessment at 2.8 years post-injury. Graph theory was applied to fMRI timeseries to evaluate the impact of TBI on global and local organisation of the resting-state network, and relevance for neurocognitive and behavioural functioning. Children with TBI showed atypical global network organisation as compared to the trauma control group, reflected by lower modularity (mild RF +  TBI and moderate/severe TBI ), higher smallworldness (mild RF +  TBI) and lower assortativity (moderate/severe TBI ps  < .04, Cohen's ds : > .6). Regarding local network organisation, the relative importance of hub regions in the network did not differ between groups. Regression analyses showed relationships between global as well as local network parameters with neurocognitive functioning (i.e., working memory, memory encoding; R 2  = 23.3 - 38.5%) and behavioural functioning (i.e., externalising problems, R 2  = 36.1%). Findings indicate the impact of TBI on global functional network organisation, and the relevance of both global and local network organisation for long-term neurocognitive and behavioural outcome after paediatric TBI. The results suggest potential prognostic value of resting-state network organisation for outcome after paediatric TBI.